The role of the symbiotic microecosystem in cancer: gut microbiota, metabolome, and host immunome - Xue, Xiaoyu; Li, Rui; Chen, Zhenni; Li, Guiyu; Liu, Bisheng; Guo, Shanshan; Yue, Qianhua; Yang, Siye; Xie, Linlin; Zhang, Yiguan; Zhao, Junning; Tan, Ruirong (Frontiers in Immunology, 2023)
The gut microbiota is not just a simple nutritional symbiosis that parasitizes the host; it is a complex and dynamic ecosystem that coevolves actively with the host and is involved in a variety of biological activities such as circadian rhythm regulation, energy metabolism, and immune response. The development of the immune system and immunological functions are significantly influenced by the interaction between the host and the microbiota. The interactions between gut microbiota and cancer are of complex nature. The critical role that guts microbiota plays in tumor occurrence, progression, and treatment is not clear despite the already done research. The development of precision medicine and cancer immunotherapy further emphasizes the importance and significance of the question of how the microbiota takes part in cancer development, progression, and treatment. This review summarizes recent literature on the on the relationship between gut microbiome and cancer immunology. The findings suggest the existence of a "symbiotic microecosystem" formed by gut microbiota, metabolome, and host immunome that is fundamental for the pathogenesis analysis and the development of therapeutic strategies for cancer.